Polytene chromosome map and inversion polymorphism in Drosophila mediopunctata - Galina Ananina; Alexandre A Peixoto; Wilma N Souza; Louis B Klaczko (Memorias do Instituto Oswaldo Cruz, 2002)
Drosophila mediopunctata belongs to the tripunctata group, and is one of the commonest Drosophila species collected in some places in Brazil, especially in the winter. A standard map of the polytene chromosomes is presented. The breakpoints of the naturally occurring chromosomal rearrangements are marked on the map. The distribution of breaking points through the chromosomes of D. mediopunctata is apparently non-random. Chromosomes X, II and IV show inversion polymorphisms. Chromosome II is the most polymorphic, with 17 inversions, 8 inversions in the distal region and 9 in the proximal region. Chromosome X has four different gene arrangements, while chromosome IV has only two.